SUPPLY CHAIN SOCIAL CAPITAL AND SUPPLY CHAIN PERFORMANCE: THE MEDIATING ROLE OF SUPPLY CHAIN INTEGRATION AND SUSTAINABILITY - Sooksai, Tommanee; Nammakhunt, Anake; Hiranphaet, Anchalee; Sinthukhammoon, Kraiwit (International Journal of Supply Chain Management, 2020)
The study has aimed to examine the impact of the supply chain social capital (SCCC) on the supply chain performance (SCHPER) of the Indonesian manufacturing firms. In addition to that the study has examined the mediating role of supply chain integration(SCHINT) and supply chain sustainability in the relationship between the supply chain social capital(SCCC) on the supply chain performance of the Indonesian manufacturing firms. The study provides empirical evidence for the role of SCI as a mediator on the relationship between social capital in supply chain and firm's performance. It has been revealed by the results that SCHINT partially or fully mediates three relations. This research was aimed at analyzing different dimensions and measures of supplier social responsibility in developing countries. There was gap in existing research studies pertaining to the empirical analysis. Social issues differ in developing countries. The complexities and capabilities specific to demand are increased with the diversity of social issues. Social issues and related dimensions are explored based on these motivations for the developing country, i.e. Indonesia. The study has used SEM-PLS for the data analysis and response rate was 80 percent. The study also explored the way in which supplier performance and supply chain performance of buyer is improved through the adoption of social sustainability practices by buyer. In a similar way, the extent to which collaboration and commitments of buyers for the social sustainability influence performance of the focal firm have been explored.